Pelatihan Pemanfaatan Buah Pala menjadi Manisan Pala yang Bernilai Jual Tinggi: Training on Nutmeg Utilization into Candied Nutmeg with High Selling Value - Jaelani, Ihrom; Purbayani, Rini; Tya, Sandi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This service is motivated by the fact that Kalijaya Village, Banjaranyar District, Ciamis Regency, is one of the potential spice-producing areas, one of which is nutmeg. This condition is not optimally utilized by the Kalijaya Village Community, especially for those who work as nutmeg farmers, where nutmeg farmers like to throw away the nutmeg meat and make it waste after taking the seeds and nutmeg pulp, even though nutmeg meat is the largest component of fresh nutmeg compared to mace, seed shell, and seed meat. Optimal utilization of nutmeg meat through diversification of nutmeg processed products such as candied nutmeg, nutmeg syrup, nutmeg candy, and many others can increase income and provide multiple benefits for nutmeg farmers in Kaijaya Village. This condition is due to the lack of understanding and skills possessed by the Kaljaya Village Community. The purpose of this service is to provide solutions for optimizing the yield of nutmeg. One of the alternatives given in solving this problem is to conduct training related to the Utilization of Nutmeg Fruit in High-Value Sweets. The method of implementing this Community Service activity is in the form of counseling, and training/practice. The service participants consisted of nutmeg farmers and members of the Kaijaya Village PKK because most of the nutmeg farmers were PKK members. The result of this service is the existence of candied nutmeg products sourced from the utilization of nutmeg meat defect waste/waste making it a new business opportunity as an additional source of income.